Peran Pendapatan Nelayan Bobo Dalam Peningkatan Kesejahteraan Keluarga - Nursal Muhammad; Arizal Hamizar; Afdhal Yaman; Dety Aryani Relubun (PT. Hafasy Dwi Nawasena, 2023)
This research aims to analyze the income of Bobo fishermen in Pulau Rhun Village in improving welfare from the perspective of Maqashid As-Syariah. The method used in this research is a descriptive qualitative method, data was obtained through direct observation through interviews, observation and documentation with Bobo fishermen in Pulau Rhun Village. The results of this research show that in general the income of bobo fishermen in Pulau Rhun Village has a great influence on family welfare. The role of fishermen's income can be measured using 3 indicators: 1) monthly income, 2) employment, and 3) family burden borne. Then, to measure the level of welfare of Bobo fishermen, 3 indicators can be used, namely: 1) basic needs of fishermen, 2) level of education, and 3) level of health. The income level of fishermen is known to influence family welfare, the existence of an income that is high enough so that bobo fishermen can meet their daily needs, can also meet the educational and health needs of their families, and are able to provide a sense of satisfaction and comfort. The Maqashid As-Syariah perspective looks at the perspective of protecting the soul, measured based on 3 aspects, namely daruriyyat, hajiyat and tasniyyat needs.